Assessment of dose capping in phenytoin loading practices in the emergency department and the impact of an emergency medicine pharmacist. Issue 6 (15th March 2019) - Holder, Martina C.; Bailey, Abby M.; Baum, Regan A.; Justice, Stephanie B.; Weant, Kyle A.
Abstract : Objectives: Phenytoin is a common anticonvulsant used for the acute treatment of seizures in the emergency department (ED). Certain patient populations, such as the obese, have been shown to present dosing challenges. Often doses are arbitrarily "capped" for fear of overdosing. Emergency medicine pharmacists (EPhs) have been shown to optimize the care of patients receiving phenytoin therapy in other settings, demonstrating reductions in seizure activity, duration of therapy, and cost. Methods: Records of patients presenting to the ED that were at least 18 years old and were prescribed intravenous phenytoin were reviewed. Patients weighing 100 kg or more were compared with those less than 100 kg. To evaluate the impact of an EPh, intravenous phenytoin orders placed during the EPh's hours were compared with those placed outside of those hours. Results: A total of 117 patients were included, 42 (36%) weighed 100 kg or more. No significant difference was found in the achievement of target (10‐20 μg/mL) postload concentrations between the two groups ( P = 0.795). Patients weighing 100 kg or more received significantly lower weight‐based phenytoin doses (16.0 vs 18.6 mg/kg, P = 0.0001). Those 100 kg or more who received less than 15 mg/kg were found to have significantly lower postload concentrations than those that received 15 mg/kg or more regardless of total dose (11.5 vs 16.5 μg/mL; P = 0.003). The presence of an EPh was found to result in significantly higher rates of postload concentrations within the therapeutic range across all groups (72.4% vs 53.7%; P = 0.04). Conclusions: The available data suggest that artificial total dose limitations in patients yield significantly lower postload concentrations, potentially delaying seizure control in the acute setting. The presence of EPhs at the bedside increases the success of initial phenytoin dosing strategies in this population.